Effectiveness of a structured ball game stimulation program on gross motor development among preschool children: a quasi-experimental study in Indonesia - Moh. Arip; Ely Mawaddah; Ade Wulandari; Mardiatun Mardiatun; Saskiyanti Ari Andini (International Journal of Public Health Science (IJPHS), 2026)
Gross motor development during ages 3-6 years is critical for children's independence and social confidence. This study induced a structured ball play stimulation program in Indonesian children using quasi-experimental design, testing the specific impact on gross motor indicators compared to local PAUD routine activities. This quasi-experimental pretest-posttest control group study assessed ball game stimulation for gross motor development in 143 preschool children in Mataram, Indonesia (intervention n = 72; control n = 71). The intervention delivered structured ball activities three times weekly for six months (August 2025-January 2026): ball introduction, throwing/catching, kicking, and group games. Controls followed the regular curriculum. Outcomes used a standardized gross motor tool. Baseline demographics were homogeneous (age p = 0.998; gender p = 0.921). Results demonstrated dramatic improvements in the intervention group, with the "Normal" category increasing from 9.72% to 94.44%, while the "Doubtful" category decreased from 83.33% to 5.56%, and "Delayed" reached 0%. Conversely, the control group showed deterioration, with "Normal" decreasing to 0% and "Delayed" increasing to 88.73%. Mann-Whitney U test confirmed statistically significant differences between groups at posttest (p = 0.000), with intervention group mean score of 1.00 versus control group 2.79. These findings provide empirical evidence that structured ball game stimulation effectively improves gross motor development in preschool children.